A Critical Companion to the 'Mirrors for Princes' Literature - Perret, Noëlle-Laetitia; Péquignot, Stéphane (Brill, 2022)
Why devote a Companion to the "mirrors for princes", whose very existence is debated? These texts offer key insights into political thoughts of the past. Their ambiguous, problematic status further enhances their interest. And although recent research has fundamentally challenged established views of these texts, until now there has been no critical introduction to the genre. This volume therefore fills this important gap, while promoting a global historical perspective of different "mirrors for princes" traditions from antiquity to humanism, via Byzantium, Persia, Islam, and the medieval West. This Companion also proposes new avenues of reflection on the anchoring of these texts in their historical realities. Contributors are Makram Abbès, Denise Aigle, Olivier Biaggini, Hugo Bizzarri, Charles F. Briggs, Sylvène Edouard, Jean-Philippe Genet, John R. Lenz, Louise Marlow, Cary J. Nederman, Corinne Peneau, Stéphane Péquignot, Noëlle-Laetitia Perret, Günter Prinzing, Volker Reinhardt, Hans-Joachim Schmidt, Tom Stevenson, Karl Ubl, and Steven J. Williams.